Measurement of Gas Diffusion Coefficient in Highly Permeable Porous Media - Levintal, E. (2020)
Gas diffusion is a fundamental transport process in porous media. However, to date, there is no method for experimentally estimating the gas diffusion coefficient of coarse porous media. A modified method is proposed here and was validated against sand media. The method was tested using particle sizes ranging between 1 and 4 cm: ∼10−3 cm2 < intrinsic permeability < ∼10−2 cm2. Laboratory experiments were conducted in large horizontal columns filled with different homogeneous spherical particles inside a climate‐controlled laboratory under isothermal (± <0.2°C) and windless conditions. Diffusion coefficients were similar for particles sizes of 1 and 2 cm, which indicates that pure diffusion governs gas transport. Above 2 cm, diffusion coefficients were higher, suggesting an enhanced gas transport, most likely initiated by small, local advective components. Because the enhanced transport can be modeled by the diffusion equation using a larger diffusion coefficient, it is associated with the enhanced diffusion concept.